EMPLOYEE JOB SATISFACTION IN MEDIATING THE RELATIONSHIP BETWEEN WORK MOTIVATION AND AFFECTIVE COMMITMENT IN ROOF TILE INDUSTRY - Romat Saragih; Bachruddin Saleh Luturlean; Ferry Hadiyanto (Jurnal Bisnis Manajemen, 2020)
This study investigated the mediation of job satisfaction in the relation between work motivation and affective commitment. An affective commitment was considered as an important factor that reflects how employees attached to their organization. An employee with high affective commitment will perform better and contribute more. It is crucial for every organization to identify factors that can drive its employees to develop affective commitment. Work motivation is considered as a factor that impacts the employee's emotional commitment towards the organization. Meanwhile, job satisfaction also believed to increases such commitment. The current study used 192 workers from the five largest roof tile manufacturers in Majalengka as participants. Using a bootstrapping approach, this study found that work motivation effects directly on job satisfaction and affective commitment. Meanwhile, job satisfaction also effects directly on affective commitment. This finding showed that job satisfaction has a mediation role in connecting work motivation and affective commitment, which was also the main finding of this research. A comparison with previous studies will be discussed, and managerial suggestions will be provided to improve employee's affective commitment.